Implantation of multiscale silk fibers on poly (lactic acid) fibrous membrane for biomedical applications. (August 2021) - Jiang, F.; Yan, D.; Lin, J.; Kong, H.; Yao, Q.
Abstract: Despite that poly (lactic acid) (PLA) has satisfactory biodegradation in vivo, its application in biomedicine is restricted due to its unsatisfactory cytocompatibility. Silk fiber (SF) has outstanding biocompatibility and silk fibroin protein obtained from silk by degumming has good hydrophilicity. Therefore, combining the PLA and silk can improve hydrophilicity of PLA to apply as biomedical materials. In this study, different concentrations of sodium hypochlorite (NaClO) were used to separate the silk to obtain multiscale silk fibers (MSFs), which were implanted into the PLA electrospun fibrous membranes (EFMs). The morphology and structure of silk fibers separated by different concentrations of NaClO were studied by Zetasizer Nano ZS, UV spectroscopy, Fourier transform infrared spectroscopy, X-ray diffraction, and scanning electron microscopy. Moreover, the biocompatibility of the surface-modified PLA composite membranes by MSFs was investigated by cell cultivation and proliferation. The results showed that the surface-modified PLA EFMs through MSF bundles obtained from NaClO split silk exhibited a certain improvement on PLA hydrophilicity and enhancement on cellular compatibility, which could have a broad prospect in the practical application of biomedical materials. Highlights: Silk fiber is oxidized into nanowires. Silk nanowires used to modify the PLA electrospun fibrous membranes. The cell compatibility of the membrane was improved.